2012
DOI: 10.1002/emmm.201101164
|View full text |Cite
|
Sign up to set email alerts
|

A complex of α6 integrin and E‐cadherin drives liver metastasis of colorectal cancer cells through hepatic angiopoietin‐like 6

Abstract: Homing of colorectal cancer (CRC) cells to the liver is a non-random process driven by a crosstalk between tumour cells and components of the host tissue. Here we report the isolation of a liver metastasis-specific peptide ligand (CGIYRLRSC) that binds a complex of E-cadherin and α6 integrin on the surface of CRC cells. We identify angiopoietin-like 6 protein as a peptide-mimicked natural ligand enriched in hepatic blood vessels of CRC patients. We demonstrate that an interaction between hepatic angiopoietin-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…It has been shown that PRL can interact with integrin proteins (71,72,73,74,75) (Figure 2). When up-regulated, PRL can dephosphorylate integrin β, enhancing integrin β binding with Src kinases (which, in turn, decreases the coupling of integrins to actin and impairs integrin-mediated adhesion) (73, 74, 75).…”
Section: Signaling Mediated By Prlmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that PRL can interact with integrin proteins (71,72,73,74,75) (Figure 2). When up-regulated, PRL can dephosphorylate integrin β, enhancing integrin β binding with Src kinases (which, in turn, decreases the coupling of integrins to actin and impairs integrin-mediated adhesion) (73, 74, 75).…”
Section: Signaling Mediated By Prlmentioning
confidence: 99%
“…When up-regulated, PRL can dephosphorylate integrin β, enhancing integrin β binding with Src kinases (which, in turn, decreases the coupling of integrins to actin and impairs integrin-mediated adhesion) (73, 74, 75). Furthermore, PRL overexpression has been shown to suppress integrin α (but not integrin β) expression levels (71,72,73,74). The down-regulation of integrin α by PRL-3 is hypothesized to be carried out via inhibition of c-fos and that integrin α binding to PRL can inhibit its interaction with the β subunit (71,72,73,74).…”
Section: Signaling Mediated By Prlmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they provide data only on the tumor cells, without taking into account their microenvironment and tumor/normal tissue interactions, which play critical roles in tumorigenesis (13). Therefore, we have recently developed a multidisciplinary approach to investigate high-risk neuroblastoma in the context of its native protein architecture, and characterized a set of specific peptide ligand motifs for neuroblastoma-targeted drug delivery in vivo (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, the differential tropism from CRC to several target sites is still not well explained, including the mechanisms that drive hepatic homing. There have been a few studies performed on liver colonization by metastatic cells [17], on the modulation of pharmacological response by the liver microenvironment [18], and on the existence of peptide ligands specific for liver metastasis [19]. However, there have been no studies in this direction involving SCLCs.…”
mentioning
confidence: 99%